by ohthatpatrick Mon Jan 20, 2014 2:14 am
I'm confused by aspects of your question, so you're probably going to have to clarify.
You initially said that if we have
A -> B
and conclude C
then one Suff Assump would be
B -> C.
That's not technically right (and although I'll explain why, it ultimately has little to do with your question).
If I have
prem: A -> B
+
Suff Assump: B ->C
Can I conclude C?
No. I can only conclude A -> B -> C
The difference here is the difference between a statement of fact and a conditional phrase.
For example, consider this argument:
(A -> B)
If Amanda comes to the party, Bob will be happy.
(conc: C)
Thus, Carmen will be happy.
Suff. Assump (B->C)
If Bob is happy, Carmen will be happy.
If you combine the premise and the SA, all you get is
If Amanda comes -> Bob is happy -> Carmen is happy.
Have you proven that Carmen will be happy?
No. You're still missing something: you need to establish that Amanda is coming to the party.
This whole conditional chain might exist, but until I know Amanda is coming, I don't know if Bob or Carmen will be happy.
However, I think this technical error had nothing to do with your real question.
Let's change the argument to this:
If Amanda comes to the party, Bob will be happy. Thus, Carmen will be happy, since Amanda will come to the party.
A -> B
A.
=====
C
The sufficient assumption here would normally be
B -> C
and the contrapositive would also be valid
~C -> ~B
(Very often the correct answer to Suff Assump is written in contrapositive form, so you should be looking out for it)
Another sufficient assumption that would work here is
A --> C
as well as its contrapositive
~C --> ~A
However, that's it.
~A --> ~C (C --> A)
would not be a sufficient assumption.
This would only help us prove that A is true, but the argument is trying to prove that C is true.
You never want to see a conditional set up as
Conclusion --> Premise
Let me know if you have questions about any of this or want to clarify what you were originally asking.